2016
DOI: 10.1097/qai.0000000000001095
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Inflammatory and Immune Activation Markers Before and After Combined Antiretroviral Therapy Initiation

Abstract: Background Women progress to death at the same rate as men despite lower plasma HIV RNA (VL). We investigated sex-specific differences in immune activation and inflammation as a potential explanation. Methods Inflammatory and immune activation markers (IFN-γ, TNF-α, IL-6, IL-18, IP-10, CRP, LPS, sCD14) were measured at weeks 0, 24, and 48 post-cART in a random subcohort (n=215) who achieved virologic suppression in ACTG A5175 (PEARLS). Association between sex and changes in markers post-cART was examined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 49 publications
0
51
0
Order By: Relevance
“…The state of the science is primarily based on largely male-dominant samples and cross-sectional studies. Given substantial evidence of sex differences in neuroimmune activation (Martin et al , 2013; Mathad et al , 2016; Ticona et al , 2015) and cognition (Failde-Garrido et al , 2008; Heaton et al , 2015; Robertson et al , 1996; Royal et al , 2016), previous findings might not be generalizable to HIV-infected women. Moreover, longitudinal studies are needed to enhance our understanding of the time course of CI in relation to altered immune function, including whether absolute levels and/or variability in these biomarkers over time relate to HIV-associated CI.…”
Section: Introductionmentioning
confidence: 78%
“…The state of the science is primarily based on largely male-dominant samples and cross-sectional studies. Given substantial evidence of sex differences in neuroimmune activation (Martin et al , 2013; Mathad et al , 2016; Ticona et al , 2015) and cognition (Failde-Garrido et al , 2008; Heaton et al , 2015; Robertson et al , 1996; Royal et al , 2016), previous findings might not be generalizable to HIV-infected women. Moreover, longitudinal studies are needed to enhance our understanding of the time course of CI in relation to altered immune function, including whether absolute levels and/or variability in these biomarkers over time relate to HIV-associated CI.…”
Section: Introductionmentioning
confidence: 78%
“…There is general consensus that starting ART early prevents or mitigates the severity of select HIV-associated comorbidities(4). Importantly, the PEARLS study, conducted in resource-limited settings, revealed that ART suppresses select indices of systemic immune activation to a lesser degree among WLHIV than among MLHIV(98). This observation may be highly relevant to sex-differences in HIV-associated non-infectious comorbidities.…”
Section: Heightened Systemic Immune Activation/inflammation Among Wlhivmentioning
confidence: 99%
“…Separate US studies among WLHIV and among MLHIV have confirmed that ART dampens select indices of systemic immune activation, albeit not down to levels seen in control subjects (40) (41) (42). Of note, however, an AIDS Clinical Trials Group study conducted in a resource-limited setting revealed that ART suppresses select indices of systemic immune activation to a lesser degree among WLHIV than among MLHIV (43). Just as ART exerts immunomodulatory effects in HIV, so too does statin therapy.…”
Section: Sex-specific Mechanisms Underlying Heightened Cvd Risk Amongmentioning
confidence: 99%